MAKNA DAN ASAL-USUL NAMA CURUG: STUDI TOPONIMI DI KABUPATEN GARUT - Maulana, Taofik (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe the meaning and origin behind the names of waterfalls in Garut Regency based on the manifestation and cultural aspects embedded within them. This research focuses on the names of various waterfalls that have been managed as natural tourist destinations in Garut Regency, then analyzed using a toponymic approach. This study uses a descriptive qualitative method, the data collection process is carried out a semi-structured interview technique with tourism managers and community leaders, as well as supporting data from the Garut Regency Tourism and Culture Office. The data studied are the names of waterfalls and the meaning behind the naming which refers to physical forms, folklore, and local myths. The results of the study show that the function of toponymy is not only as a geographical marker, but also as a cultural documentation in which there is collective memory, local identity, and spiritual values of the surrounding community. Some waterfall names related to local beliefs in the form of prohibitions indirectly play a role in preserving the values of local wisdom and the natural environment around the waterfall.